2020
DOI: 10.1021/acsnano.0c00366
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Peapod-like Sb@C and Corn-like C@Sb Nanotubes for Sodium Storage

Abstract: Antimony (Sb) is regarded as an attractive anode material for sodium-ion batteries (SIBs) due to its high theoretical capacity of 660 mAh g–1. Combining Sb with carbonaceous materials has been considered as an effective way to resolve the serious volume expansion issues. Sb/C composites mainly consist of two types, that is, Sb confined inside a carbon matrix and Sb deposited on the surface of a carbon matrix, and both have shown superior sodium storage performance. However, which structure is more beneficial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 64 publications
2
66
0
1
Order By: Relevance
“…[ 5 ] These voids should be advantageous for accommodating the volume expansion during the sodiation/desodiation processes. [ 24 ] The transmission electron microscopy (TEM) image (Figure 1e) again reveals the core‐shell‐like structure of NCOS. According to the high‐resolution TEM (HRTEM) image (Figure 1f), the nanoparticles dispersed in the inner region of NCOS nanowire are highly crystalline with the size of about 10 nm, while the outer shell is an obvious layer with a thickness of ≈30 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[ 5 ] These voids should be advantageous for accommodating the volume expansion during the sodiation/desodiation processes. [ 24 ] The transmission electron microscopy (TEM) image (Figure 1e) again reveals the core‐shell‐like structure of NCOS. According to the high‐resolution TEM (HRTEM) image (Figure 1f), the nanoparticles dispersed in the inner region of NCOS nanowire are highly crystalline with the size of about 10 nm, while the outer shell is an obvious layer with a thickness of ≈30 nm.…”
Section: Resultsmentioning
confidence: 99%
“…To address these issues, many strategies have been proposed, such as designing new nanostructures (e.g., Sb nanotubes, [39] antimonene, [40,41] and nanoporous Sb [42][43][44] ), forming Sb-based intermetallics (e.g., SbSn, [45][46][47][48] SbNi, [49,50] and SbBi [51,52] ) and constructing protective layers (e.g., TiO 2 , [53][54][55] Co(OH) 2 , [56] and carbon [57][58][59][60][61][62][63][64][65][66][67][68][69] ). Among these approaches, constructing a protective layer has been regarded as the most effective way to solve the volume expansion problems.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] Besides the improved electronic conductivity, carbon coating also inclined to prevent particle aggregation and pulverization. [30,31] In addition, introducing a porous structure into the composite may be another effective way to stabilize the cycle performance. For example, Jeong et al reported that compared with the bulk material that prepared by the same method, the porous sample synthesized in situ by removing the template in the composite was able to release severe mechanical stress during the charge-discharge process, accelerate the penetration of electrolyte, and provide abundant reactive sites.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the selenide anode materials with carbon materials is an effective way of buffering the volume expansions during the insertion procedure [26–29] . Besides the improved electronic conductivity, carbon coating also inclined to prevent particle aggregation and pulverization [30,31] . In addition, introducing a porous structure into the composite may be another effective way to stabilize the cycle performance.…”
Section: Introductionmentioning
confidence: 99%